Can Critical-thinking Skills be Measured by Analyzing Metacognition? - Alpindo, Okta; Istiyono, Edi

(untitled) - Andriyanti, Erna (Journal of Teaching and Learning)

(untitled) (University of Windsor, 2024)
Metacognition refers to the capacity to comprehend and manage one's own cognitive processes, enabling the recognition of biases and presumptions that might influence them. Numerous published studies indicate that through metacognition, enhancements in critical-thinking skills allow individuals to query information, assess data, and make more evidence-grounded decisions—a cornerstone of critical and analytical thinking. This study aims to delineate the association between metacognition and critical-thinking skills via a meta-analysis. The data sources encompass articles published on Scopus between 2013 and 2023, identified using the keywords "Metacogni*" AND "Critical Thinking". This meta-analysis included 60 studies from diverse global locations. Employing a random-effects model, the analysis evaluated both effect size and potential publication biases using Jamovi 2.2.5 and OpenMEE software. The outcomes affirm a significant correlation between metacognition and critical-thinking skills, highlighting a robust effect of metacognition on critical-thinking skills, reflected in a significant measure of r = 0.649. Thus, increasing metacognitive abilities will improve critical-thinking abilities.